Variance of Ks distribution corrects the bias in the divergence caused by the ancestral population size - Li, Mi-Jia; Li, Xiao-Xue; Xu, Lin-Lin; Zhang, Bo-Wen (Frontiers in Genetics, 2025)
Ks distribution, the distribution of the synonymous substitutions, has been widely used to estimate the species divergence using orthologous genes. However, conventional approaches often ignore the underlying bias that species divergence is delayed to average gene divergence by 2Ne generations, where Ne represents the ancestral effective population size, due to the lack of scalable methods for Ne inference. Here, we demonstrate through simulations that Ks distribution variance correlates with Ne, enabling direct estimation of ancestral population parameters from standard Ks data. Leveraging this relationship, we present Tspecies, a framework that corrects divergence time estimates using only substitution rates and Ks distributions, without requiring additional genomic data. Our practical application of Tspecies in Liriodendron has inferred a divergence time between North American and East Asian lineages (1.44 Ma) that align with early Pleistocene glaciation, and a large ancestral Ne (∼5.29 × 104) consistent with fossil evidence. Our finding reveals the correlation between the variance of Ks distribution and Ne, and develops a computational framework to resolve the bias in Ks based dating by incorporating a readily estimated Ne.